2016
DOI: 10.1186/s12888-016-1018-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive change is more positively associated with an active lifestyle than with training interventions in older adults at risk of dementia: a controlled interventional clinical trial

Abstract: BackgroundWhile observational studies show that an active lifestyle including cognitive, physical, and social activities is associated with a reduced risk of cognitive decline and dementia, experimental evidence from corresponding training interventions is more inconsistent with less pronounced effects. The aim of this study was to evaluate and compare training- and lifestyle-related changes in cognition. This is the first study investigating these associations within the same time period and sample.MethodsFif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 63 publications
1
55
0
5
Order By: Relevance
“…Furthermore, an active lifestyle includes the variety of physical, cognitive and social activities. Also, a stronger relationship of lifestyle with memory, but not with other cognitive functions like for example executive functions [5]. The relevance of lifestyle factors is in line with another meta-analysis [6] showing that cognitively stimulating leisure activities may contribute to a reduced risk of cognitive impairment in later life.…”
Section: Commentarysupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, an active lifestyle includes the variety of physical, cognitive and social activities. Also, a stronger relationship of lifestyle with memory, but not with other cognitive functions like for example executive functions [5]. The relevance of lifestyle factors is in line with another meta-analysis [6] showing that cognitively stimulating leisure activities may contribute to a reduced risk of cognitive impairment in later life.…”
Section: Commentarysupporting
confidence: 55%
“…Küster et al [5] showed, in a controlled intervention study, that a cognitive improvement in older adults at risk of dementia is more positively associated with an active cognitive lifestyle as with a specific cognitive or physical training program. More specifically, adults with an active lifestyle as measured by their physical, cognitive and social activity, showed an improvement in cognitive performance after ten weeks compared to individuals with a less active lifestyle.…”
Section: Commentarymentioning
confidence: 99%
“…The training consisted of six different tasks targeting auditory processing and working memory (for details see Mahncke et al, 2006a,b; Küster et al, 2016). In each session, four different 15-min training tasks were completed.…”
Section: Methodsmentioning
confidence: 99%
“…Mitigating cognitive decline via cognitive development likely requires a favorable lifestyle approach that includes a number of factors working together to encourage cascading patterns of positive thoughts and actions [Friedman & Martin, 2011;Küster et al, 2016;Marzorati, 2016]. An aim of this framework is to inform cognitive interventions with aging adults to induce a lifestyle change.…”
Section: Theoretical Considerationsmentioning
confidence: 99%